2011
DOI: 10.1021/mp100305h
|View full text |Cite
|
Sign up to set email alerts
|

Lecithin-Based Novel Cationic Nanocarriers (Leciplex) II: Improving Therapeutic Efficacy of Quercetin on Oral Administration

Abstract: The objective of the present investigation was to evaluate ability of the novel self-assembled phospholipid- based cationic nanocarriers (LeciPlex) in improving the therapeutic efficacy of a poorly water-soluble natural polyphenolic agent, quercetin (QR), on oral administration. Quercetin loaded LeciPlex (QR-LeciPlex) were successfully fabricated using a biocompatible solvent Transcutol HP. The QR-LeciPlex were characterized for particle size, encapsulation efficiency, zeta potential, and particle morphology b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 50 publications
(118 reference statements)
1
39
1
Order By: Relevance
“…In this situation, external supply of antioxidants is essential to counter balance the dangerous effects of oxidative stress. It is evident that flavanoid antioxidants like quercetin have potential role in ROS scavenging in the pathogenesis of diabetes, which can also delay the oxidative injury and cell death [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, external supply of antioxidants is essential to counter balance the dangerous effects of oxidative stress. It is evident that flavanoid antioxidants like quercetin have potential role in ROS scavenging in the pathogenesis of diabetes, which can also delay the oxidative injury and cell death [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…However, pharmaceutically, quercetin is a challenging molecule to be delivered due to its poor solubility, low hydrophilicity (log P of 1.81), gastrointestinal instability, extensive first pass metabolism, and minimal absorption in gastrointestinal tract [2]. Quercetin belongs to BCS class II.…”
Section: Introductionmentioning
confidence: 99%
“…Oils and lipids are also important excipients employed in preclinical studies. Lecithin is a well-known stabilizer used in preclinical suspensions and emulsions and is known for its potential to improve oral absorption by increasing micellization of drugs in GIT (110,115). Many long-chain triglycerides and medium-chain triglycerides used as either the oil component of emulsions or as stabilizers are known to exert similar effects.…”
Section: Excipientsmentioning
confidence: 99%
“…This has been achieved through specialized uptake mechanisms, increased half-life (t 1/2 ), minimized toxicity, and increased ability of NPs to cross the physiological barriers such as the BBB. 9,10 To improve the oral bioavailability of QT, various attempts have been made by many researchers to formulate various drug delivery systems of current drug therapy, such as poly(D,L-lactide) (PLA) NPs, 7 solid lipid NPs, 8 lecithin-based novel cationic nanocarriers (LeciPlex), 11 chitosan NPs, 12 liposomes, 13 and poly(D,L-lactide-co-glycolide) (PLGA) NPs, 14 but all with limited effects. However, no detailed study has been reported on improving the brain permeability of the drug.…”
Section: Introductionmentioning
confidence: 99%